Layer-4 Load Balancer on Programmable Data Plane using IP Hash and Weighted Round Robin - Muchlis Ramadhan Usman; Nugroho, Muhammad Arief; Ibnu Asror (LOGIC: Jurnal Penelitian Informatika, 2025)
Layer-4 load balancer used in data center to distribute requests coming from client to multiple servers located in data center. There are two requirements to build proper Layer-4 load balancing. The first is ensuring the uniformity of request distribution across multiple servers and connection affinity. IP Hash is a common load balancing algorithm that is used to implement Layer-4 load balancing but can cause load imbalances across multiple servers. Weighted Round-Robin is proposed to prevent load imbalance across multiple servers. The implementation of load balacing is using a programmable data plane rather than additional hardware or software load balancing. The result shows that WRR is able to mitigate load imblance across multiple servers by achieving uniform request distribution. WRR achieves 13% higher throughput but gives 2% higher response times than IP Hash and has less packet loss than IP Hash when handling HTTP requests.